Penggunaan Strategi Murder dalam Pembelajaran Pendiidkan Agama Islam di Sekolah Dasar Negei 6 Penujak Lombok Tengah Tahun Pelajaran 2018 - Bq. Hadia Martanti (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
The purpose of this study was to determine the effect of the MURDER strategy on the learning outcomes of students' Islamic religious education. This research is an experimental research. The subject of the study were 52 grade V students of SDN 6 penujak, 30 female students and 22 male students. This study is a quasi-experimental study that uses two samples, namely the experimental group and the control group. The data planning method used is an objective form test. The results of the study showed that the experimental group learning outcomes were more increased than the control group learning outcomes. After analyzing the data about learning using MURDER strategy in the study program the average value of students was 75.4 with a completeness percentage of 85% while the average value of students who used the conventional method reached 66.8 with a completeness percentage of 68%. Based on the results of the study, it can be concluded that the MURDER strategy has a positive effect on students' mathematics learning outcomes compared to learning using conventional methods.